OHP-019 Reorganisation of a permanent sterile osteosynthesis implants store. (24th February 2014) - Duprès, M; Bondon, AC; Pignon, A; Wolber, O; Moreau, C
Abstract : Background: 3 years after a permanent sterile osteosynthesis implants store was created and faced with an increasingly busy surgical unit, changes in surgical practice and the arrival of new healthcare staff, it seemed essential to us to reorganise this stock. Purpose: To respond to the needs of the surgical unit team for sterile osteosynthesis implants (SOI). Materials and methods: The store was reorganised in 4 steps: Assessment of the number of SOI held in stock and the number used over the last 12 months Categorisation of the implants according to their turnover rate (TR): (TR = the number of implants used in a year/ (12 x the number of these implants in stock) (number of times that a SOI is used monthly) 0≤TR <0.176: class A = SOI with low turnover - > stock reduction 0.176≤TR <0.353: class B = SOI with medium turnover - > unchanged stock TR≥: class C = SOI with greater turnover - > stock increased Calculation of a proposal for a new store based on an ideal TR = 0.26 Discussion about the proposal with the surgeons. Results: The permanent store holds 384 items covering 2300 SOI. The classes A, B and C respectively contain: 367, 11 and 6 items, that means 2092 SOI in class A, 128 in class B and 80 in class C. Regarding class A, the number of SOI decreased in 77.6% of the items (924 SOI were counted after optimisation). 144 items have been deleted. With reference to class B, 18.2% of the store remains unchanged (139 SOI in this class after optimisation). An increase in SOI has been reported for 50% of the class C items (87 SOI after optimisation). Thanks to the TR, a stock proposal has been formulated, optimised and approved with the surgeons. Conclusions: This reorganisation was possible because the osteosynthesis implants were sterile. This optimisation of the permanent sterile osteosynthesis implants store allowed us to reduce our store by half (from 2300 to 1150 SOI). We also made a contract for the new store with the surgical unit team enabling us to improve the safety of osteosynthesis implants system. No conflict of interest.